Construction of the Indonesian Presidents’ Speeches at the UN: Historical Discourse Analysis - Risaldi, Antok; Santoso, Anang (Universitas Muhammadiyah Malang, 2024)
The construction of the speeches of the four presidents lies at the complex intersection of sociohistorical practices, where the disciplines of psychology, political science, history, sociology, and anthropology were formed. The aim of this study was to analyze the corpus-based construction of the Indonesian Presidents’ speech at the UN. This research method used a descriptive approach. This type of qualitative research was oriented towards historical discourse analysis. This research data consisted of words, phrases, and sentences obtained from speeches by four Indonesian presidents at the UN. The data corpus of the four Indonesian presidents' speeches was obtained from the YouTube channel. The collection of corpus data in this research was carried out through observation to find out whether the videos of the four presidents' speeches were sound and complete. The available data corpus was analyzed based on Wodak's analysis of historical discourse (HDA). The research results indicated that the construction of the four Indonesian presidents’ speeches at the UN included the use of discursive strategies, namely argumentation and nomination. The findings of this research also showed that the argumentation strategy used topics that were divided into the past, present, and future. This topic refers to intrinsic topics in the form of reality, economy, justice, health and urgency, while extrinsic topics include reality, history, economics, threats, justice, health, and urgency. The nomination strategy found the use of personal deixis in the form of I, we, and us as identity markers in the Indonesian presidents’ speeches at the UN. The conclusion of this research indicated that the topic analysis and identity markers used by the four Indonesian presidents were different. This can be seen from the use of the number of words that appear in the four speech data corpus, which showed how the four presidents opened their talks and how they identified themselves, defined their countries, and described their attitudes.